Optimizing Road Pavements with Coal Tar: A Novel Approach to Granular Base Stabilization - R Ochoa Díaz; A Montañez; J Cuentas (Contemporary Perspective on Science, Technology and Research Vol. 6, 2024)
Upon seeing the current state of roads in the country, in which high investments are made and the pavement structures do not support the period of time for which they are constructed, it becomes necessary to search for new construction and stabilization methods for pavement which comply with construction specifications. This study shows the role of an alternative in granular base stabilization, such as coal tar. Coal tar is a by-product of coal distillation in the absence of oxygen to obtain metallurgical coke; its colour varies from dark coffee to black, slightly viscous and its density is greater than that of water. Taking into account the previous characteristics, this study also presents the feasibility of using coal tar for the improvement of physical properties, mechanics and dynamics of materials used in road engineering. The coal tar used in this study is produced in the steel Acerías Paz del Río S.A. In this way, the origin, characteristics, and properties of tar are first described. Next, its combination with granular-based material is evaluated through the CBR test procedure to determine its resistance and to compare it with the non-stabilized material. Finally, the behaviour of the material when subjected to dead loads by means of resistant modules found with the NAT (Nottingham Asphalt Tester) is explored. As a result, the option of using coal tar as a stabilizer was identified due to its use under specific conditions.